Acute thermal stress alters sperm swimming activity, viability, and gene expression in blue catfish, Ictalurus furcatus - Kaylan M. Price; Brian G. Bosworth; Samitha S.N. Liyanage; Jason W. Abernathy; Benjamin H. Beck; Luke A. Roy; Timothy J. Bruce; Rex A. Dunham; Ian A.E. Butts (Theriogenology, 2026)

A lightweight and inexpensive percussion-coring system for shallow (< ~ 4 m-depth) ice-covered lakes - Jason R. Price (Journal of Paleolimnology, 2026)

Behavioral variation across multiple phases of intravenous cocaine self-administration among genetically diverse mouse populations - Price E. Dickson; Udita Datta; Troy D. Wilcox; Ashley A. Auth; Robyn L. Ball; Matt Dunn; Heidi S. Fisher; Alyssa Klein; Michael R. Leonardo; Tyler A. Roy; Michael C. Saul; Jason A. Bubier; et al. (Psychopharmacology, 2026)
Genetic and other predisposing factors can influence the progression from initiation of drug intake to compulsive substance use through distinct biobehavioral processes. Operant cocaine self-administration studies in laboratory mice offer a powerful method to dissect the biology of this progression from initiation, dose-response, extinction, and cued reinstatement in a controlled, tractable system. However, many such studies encompass limited genetic diversity and rarely examine self-administration behaviors beyond the acquisition stage. Here, we study three high-diversity mouse populations – 50 strains from the Collaborative Cross (CC) reference panel, a large sample of Diversity Outbred (J: DO) population and their eight founder strains – to characterize the varied phenotypic manifestation of behaviors across multiple phases of cocaine intravenous self-administration (IVSA) in both sexes. We observed distinct strain differences among the founders and CC strains in all phases of self-administration, with heritability estimates ranging from 0 to 0.585 and many CC and J: DO phenotypic values exceeding the range of founders including the C57BL/6J strain. Sex differences were common across behaviors, some manifesting as main effects, others as strain interactions. Finally, by adopting a multi-stage design, we identified extreme strains for various cocaine intake and response traits. Together, these findings demonstrate the utility of extended self-administration protocols in high-diversity mouse populations and establish feasibility for their use in the discovery and characterization of biological mechanisms of substance use traits and for preclinical studies in relevant, complex mouse models.

Decoupling between silicate and phosphate mineral weathering in the granitic periglacial weathering-limited landscape of the Loch Vale watershed, Rocky Mountain National Park, Colorado, USA - Jason R. Price; Suzanne Bricker; Emerson Andelt; James Kinnison (Chemical Geology, 2026)

A decision support tool for assessing entanglement risk to protected species from fixed-gear fisheries with applications to North Atlantic right whales (Eubalaena glacialis) in the Northwest Atlantic - Burton Shank; Alicia S. Miller; Laura Solinger; Michael J. Asaro; Douglas Sigourney; Alessandra Huamani; Marisa L. Trego; Crystal Franco; Jason J. Roberts; Jeffrey D. Walker; André L. Price; Mareike D. Duffing Romero; et al. (Frontiers in Marine Science, 2025)
Entanglement is one of the primary anthropogenic threats to the North Atlantic right whale ( Eubalaena glacialis ; right whale) whose habitat overlaps fixed-gear fishing grounds in the Northwest Atlantic with entanglements representing around half of the mortality and serious injury incidents. Right whale mortality has reached levels that require intervention under the Marine Mammal Protection Act, creating the need for a tool that can compare the relative benefits of risk reduction management measures under consideration. To address this need, National Marine Fisheries Service developed a Decision Support Tool (DST) which has undergone continued development since 2019 and is introduced here as the Woods Hole Analysis of Line Entanglement (WHALE) DST. This tool calculates relative risk as the product of (1) the density of endlines associated with fixed-gear fishing at a given location and month, (2) the entanglement severity that endlines pose based on the specific configuration of the gear, and (3) the estimated density of right whales at the given location and month. The model is novel in its capacity to quantify reductions in entanglement risk by simultaneously assessing a variety of overlapping management actions such as time/area closures, weakening of rope, and other adaptations of gear configurations that reduce endlines or make them less dangerous. We demonstrate the functionality of the WHALE DST by applying management actions implemented in 2021. While originally developed for right whale conservation, the WHALE DST is adaptable for evaluating spatiotemporal entanglement risk reduction for other protected species management and marine spatial planning activities.

Mineral chemistry, ASTER hydrothermal alteration mapping, and geotechnical characterization of granitic rocks of the Arabian-Nubian Shield; A case study from Wadi El-Hima, South Eastern Desert, Egypt - Ahmed M. Abdel-Rahman; Hisham A. Gahlan; Mahmoud L. Abdel Latif; Mahmoud H. Elyaseer; Jason B. Price; Mokhles K. Azer (Journal of African Earth Sciences, 2025)

Carboxymethyl cellulose biodegradation by activated sludge microbial communities - Ashley Wilcox; Maura Hall; Jennifer Menzies; Nigel Yates; Jason Price; Taylor Neal; Spiro Stilianoudakis; Sandra Isaacs; Yiping Sun; Mark Sivik; Kathleen McDonough (Science of The Total Environment, 2025)

Field experiments on the effects of fire on parasite transmission to amphibian hosts - Nicole Ortega; Alexander Shepack; Wayne Price; Todd Campbell; Kym Rouse Holzwart; Steven A. Johnson; Jason R. Rohr (Ecology, 2025)
The emergence of infectious diseases is often associated with changes to host–pathogen ecology, and wildfires are known to profoundly modify the ecology of terrestrial and freshwater ecosystems. Nevertheless, few studies have employed manipulative experiments to quantify the effects of fire on infections across parasite species. In a mark–recapture study, prescribed burns did not significantly affect the densities of Cuban tree frog (CTF; Osteopilus septentrionalis ) definitive hosts. However, prescribed burn field experiments and a before‐after‐control‐burn mesocosm study revealed that fire decreased a skin‐penetrating nematode in CTFs by killing the parasite's soil‐dwelling, free‐living stage, with hotter fires causing a greater reduction in soil‐dwelling nematodes. Additionally, prescribed burns were associated with increases in a terrestrial acuariid nematode and several aquatic trematode metacercariae in CTFs, likely by increasing intermediate host densities. Seven years after the burns, we found little evidence of full recovery because the trajectories of these parasites did not show clear signs of flattening. These results suggest that fire can have predictable and long‐term direct and indirect positive and negative effects on parasite transmission.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Deployment-invariant probability of detection characterization for aerial LiDAR methane detection - Michael J. Thorpe; Aaron Kreitinger; Dominic T. Altamura; Cameron D. Dudiak; Bradley M. Conrad; David R. Tyner; Matthew R. Johnson; Jason K. Brasseur; Peter A. Roos; William M. Kunkel; Asa Carre-Burritt; Jerry Abate; et al. (Remote Sensing of Environment, 2024)

Drinking water sources, quality, and associated health outcomes in Appalachian Virginia: A risk characterization study in two counties - Alasdair Cohen; Md Rasheduzzaman; Bethesda O'Connell; Teresa Brown; Mami Taniuchi; Leigh-Anne Krometis; Alan Hubbard; Phillip Scheuerman; Marc Edwards; Amanda Darling; Blaine Pennala; Sarah Price; et al. (International Journal of Hygiene and Environmental Health, 2024)

Community science informs movement and reproductive ecology of sand tigers Carcharias taurus off North Carolina, United States of America - Carol Seals Price; Ara Lupton McClanahan; Erin J. Burge; Tanya Houppermans; Jason Holmberg (Frontiers in Marine Science, 2024)
Sand tigers are frequently observed at shipwrecks and other artificial reef habitats off North Carolina (USA), but data about occupancy, movement ecology, and site fidelity are lacking. Spot A Shark USA researchers used Wildbook © photoidentification software to spot map sand tigers in images provided by recreational SCUBA divers, or collected from remotely operated vehicles, and an offshore live-streaming camera. We uniquely identified 1837 sand tigers, 101 of which were resighted on more than one date between 2005–2021. Sand tigers of both sexes and various ages were found year-round along the northern, central and southern coast. We identified shipwrecks or artificial reef sites with consistently high numbers of shark encounters reported, sometimes with seasonal occupancy patterns. Resighted sharks were often encountered at the same or nearby locations, confirming high levels of residency and site fidelity to specific locations. Together, the mating scars seen on 121 female sand tigers and 202 females documented with rotund abdomens consistent with pregnancy highlight the importance of NC waters for reproduction. We also quantified other characteristics of the sand tigers visible in the photographs including wounds, parasitic copepods, and attached fishing gear. Our results reflect the importance of habitats off the NC coast to the movement and reproductive ecology of sand tigers at multiple life history stages. Sand tiger populations have declined in the Northwest Atlantic, so information about residence at specific locations, seasonal patterns of occupancy, and sex-dependent behaviors associated with migration and reproduction are important to future management and conservation of the species.

Elucidating the performance of UV-based photochemical processes for the removal of trace organic contaminants: Degradation and toxicity evaluation - Arbab Tufail; Jawad Al-Rifai; William E. Price; Jason P. van de Merwe; Frederic D.L. Leusch; Faisal I. Hai (Chemosphere, 2024)

Mineralogy, geochronology, and geochemistry of the calc-alkaline Um Takha white granite pluton, South Sinai, Egypt - Madiha S.M. Osman; Mokhles K. Azer; Paul D. Asimow; Jason B. Price; Mauricio Ibañez-Mejia (Lithos, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

CT slice alignment to whole-body reference geometry by convolutional neural network - Price Jackson; James Korte; Lachlan McIntosh; Tomas Kron; Jason Ellul; Jason Li; Nicholas Hardcastle (Physical and Engineering Sciences in Medicine, 2021)

Geological fracture mechanics - Jason B. Price (International Geology Review, 2021)

Critical land change information enhances the understanding of carbon balance in the United States - Jinxun Liu; Benjamin M. Sleeter; Zhiliang Zhu; Thomas R. Loveland; Terry Sohl; Stephen M. Howard; Carl H. Key; Todd Hawbaker; Shuguang Liu; Bradley Reed; Mark A. Cochrane; Linda S. Heath; et al. (Global Change Biology, 2020)
Large‐scale terrestrial carbon (C) estimating studies using methods such as atmospheric inversion, biogeochemical modeling, and field inventories have produced different results. The goal of this study was to integrate fine‐scale processes including land use and land cover change into a large‐scale ecosystem framework. We analyzed the terrestrial C budget of the conterminous United States from 1971 to 2015 at 1‐km resolution using an enhanced dynamic global vegetation model and comprehensive land cover change data. Effects of atmospheric CO 2 fertilization, nitrogen deposition, climate, wildland fire, harvest, and land use/land cover change (LUCC) were considered. We estimate annual C losses from cropland harvest, forest clearcut and thinning, fire, and LUCC were 436.8, 117.9, 10.5, and 10.4 TgC/year, respectively. C stored in ecosystems increased from 119,494 to 127,157 TgC between 1971 and 2015, indicating a mean annual net C sink of 170.3 TgC/year. Although ecosystem net primary production increased by approximately 12.3 TgC/year, most of it was offset by increased C loss from harvest and natural disturbance and increased ecosystem respiration related to forest aging. As a result, the strength of the overall ecosystem C sink did not increase over time. Our modeled results indicate the conterminous US C sink was about 30% smaller than previous modeling studies, but converged more closely with inventory data.

Zincoberaunite, ZnFe3+ 5(PO4)4(OH)5⋅6H2O, a new mineral from the Hagendorf South pegmatite, Germany - Nikita V. Chukanov; Igor V. Pekov; Ian E. Grey; Jason R. Price; Sergey N. Britvin; Maria G. Krzhizhanovskaya; Anthony R. Kampf; Bernhard Dünkel; Erich Keck; Dmitry I. Belakovskiy; Colin M. MacRae (Mineralogy and Petrology, 2017)

Systems genetics of intravenous cocaine self-administration in the BXD recombinant inbred mouse panel - Price E. Dickson; Mellessa M. Miller; Michele A. Calton; Jason A. Bubier; Melloni N. Cook; Daniel Goldowitz; Elissa J. Chesler; Guy Mittleman (Psychopharmacology, 2016)

Climate change risks to US infrastructure: impacts on roads, bridges, coastal development, and urban drainage - James E. Neumann; Jason Price; Paul Chinowsky; Leonard Wright; Lindsay Ludwig; Richard Streeter; Russell Jones; Joel B. Smith; William Perkins; Lesley Jantarasami; Jeremy Martinich (Climatic Change, 2015)

Ocean and Coastal Acidification off New England and Nova Scotia - Dwight Gledhill; Meredith White; Joe Salisbury; Helmuth Thomas; Ivy Misna; Matthew Liebman; Bill Mook; Jason Grear; Allison Candelmo; R. Christopher Chambers; Christopher Gobler; Christopher Hunt; et al. (Oceanography, 2015)

Development of polymorphic microsatellite markers for the bonnethead shark, Sphyrna tiburo - Kimberly A. Price; Jason R. O’Bryhim; Kenneth L. Jones; Stacey L. Lance (Conservation Genetics Resources, 2015)

Into and out of the tropics: the generation of the latitudinal gradient among New World passerine birds - Jonathan D. Kennedy; Zhiheng Wang; Jason T. Weir; Carsten Rahbek; Jon Fjeldså; Trevor D. Price (Journal of Biogeography, 2014)
Aim One prominent explanation for the latitudinal gradient in biodiversity proposes that its prime cause is the greater age and/or higher origination rates of tropical clades, and the infrequent or delayed dispersal of their component species into temperate regions. An alternative is that species’ carrying capacities vary regionally, which influences rates of time‐averaged diversification via ecological opportunity. We contrast these hypotheses, in order to assess potential historical influences upon the latitudinal gradient of New World passerine birds (order Passeriformes), comparing patterns among the two suborders present (oscines and suboscines), which are known to have had different routes of dispersal across the region. Location New World. Methods We examine diversity patterns, their abiotic and biotic correlates, and the distributions of phylogenetically old and young species. Results Strong latitudinal gradients are present within both oscine and suboscine birds, with maximum diversity towards the equator, but their overall shapes differ. Among the oscines, older lineages are found towards the north, with progressively younger lineages present further south. Regional variation in oscine richness is statistically well explained by a combination of productivity and elevation ( R 2 = 0.76). In contrast, few suboscine groups have colonized the north, so their current diversity is well correlated with temperature seasonality ( R 2 = 0.74). Main conclusions Because the oscines colonized the Americas from the north, their latitudinal gradient must reflect regional differences in time‐averaged diversification rates, and not the time present within a region. The richness patterns derived from phylogenetic data and the strong predictive power of the normalized difference vegetation index (NDVI) suggest that the radiation of the oscines is consistent with the idea that entry into a new region stimulates a burst of diversification, which is higher and/or continues for longer in areas with greater carrying capacity. Conversely, the suboscine distributions potentially reflect a large historical barrier to dispersal and niche conservatism of climatic tolerances, possibly coupled with competition from the oscines. Although contemporary conditions can explain much of the passerine diversity patterns, history has had an important influence on the taxonomic composition of this gradient.

The biogeography and filtering of woody plant functional diversity in North and South America - Nathan G. Swenson; Brian J. Enquist; Jason Pither; Andrew J. Kerkhoff; Brad Boyle; Michael D. Weiser; James J. Elser; William F. Fagan; Jimena Forero‐Montaña; Nikolaos Fyllas; Nathan J. B. Kraft; Jeffrey K. Lake; et al. (Global Ecology and Biogeography, 2012)
Aim In recent years evidence has accumulated that plant species are differentially sorted from regional assemblages into local assemblages along local‐scale environmental gradients on the basis of their function and abiotic filtering. The favourability hypothesis in biogeography proposes that in climatically difficult regions abiotic filtering should produce a regional assemblage that is less functionally diverse than that expected given the species richness and the global pool of traits. Thus it seems likely that differential filtering of plant traits along local‐scale gradients may scale up to explain the distribution, diversity and filtering of plant traits in regional‐scale assemblages across continents. The present work aims to address this prediction. Location North and South America. Methods We combine a dataset comprising over 5.5 million georeferenced plant occurrence records with several large plant functional trait databases in order to: (1) quantify how several critical traits associated with plant performance and ecology vary across environmental gradients; and (2) provide the first test of whether the woody plants found within 1° and 5° map grid cells are more or less functionally diverse than expected, given their species richness, across broad gradients. Results The results show that, for many of the traits studied, the overall distribution of functional traits in tropical regions often exceeds the expectations of random sampling given the species richness. Conversely, temperate regions often had narrower functional trait distributions than their smaller species pools would suggest. Main conclusion The results show that the overall distribution of function does increase towards the equator, but the functional diversity within regional‐scale tropical assemblages is higher than that expected given their species richness. These results are consistent with the hypothesis that abiotic filtering constrains the overall distribution of function in temperate assemblages, but tropical assemblages are not as tightly constrained.

Lithium overdose with electrocardiogram changes suggesting ischemia - Joshua Puhr; Jason B. Hack; Jacquelyn A. Early; William L. Price; William J. Meggs (Journal of Medical Toxicology, 2008)

Responses against complex antigens in various models of CD4 T-cell deficiency - Yifan Zhan; Lorena E. Brown; Georgia Deliyannis; Shirley Seah; Odilia L. Wijburg; Jason Price; Richard A. Strugnell; Phillip J. O’Connell; Andrew M. Lew (Immunologic Research, 2004)

Fitness and evolution in clonal plants: the impact of clonal growth - Jean J. Pan; Jason S. Price (Evolutionary Ecology, 2001)